The Effect of the First Italian Research Evaluation Exercise on Student Enrolment Choices - Daniele Biancardi; Massimiliano Bratti (Institute of Labor Economics (IZA), 2018)
This paper studies the impact of the first Italian Research Evaluation Exercise (VTR 2001-2003) on university undergraduate students' enrolment choices. A before-after estimator with differential treatment intensities is used to investigate whether subject-group higher education institutions (HEIs) that had a higher performance in the VTR also benefited from more student enrolments and enrolment of students with better entry qualifications after the VTR. Our analysis demonstrates that increasing the percentage of "excellent" research products by one standard deviation (19 percentage points) increases student enrolment by 5.8%. The effects are larger for high-quality students, namely those with better high school final marks (8.3%) or coming from the academic track (12.2%), and they are larger for subject-group HEIs in the top quartile of the VTR quality distribution. The effects are of similar magnitude across all macro-regions (North, Centre and South and Islands), but they are precisely estimated only for universities in the North. When HEIs are divided into new and old universities, only the former, which have less established reputations in teaching and research, appear to have gained from good performance in the VTR.
Keywords: I21; I23; 330; research evaluation exercise; student enrolment; student quality; Italy; VTR